A particle image velocimetry investigation of the flow field close to a heave plate for models of different scales. (December 2022) - Saettone, Simone; Molinelli Fernandez, Enrique; Soriano Gómez, Cristina; Saavedra Ynocente, Leandro Antonio; Duque Campayo, Daniel; Souto-Iglesias, Antonio; Maron Loureiro, Adolfo
Abstract: Semi-submersible floating wind turbines are generally equipped with heave plates to introduce additional hydrodynamic damping and decrease the platform's natural frequency. Scale effects are one of the most critical problems concerning the accuracy of model-scale experiments on these damping-augmenting devices. The current research aimed to assess the impact of the scale factor on the flow physics of oscillating circular solid plates. Forced oscillation flow visualisation model-scale experiments were performed on three geometrically similar one-leg columns of a semi-submersible platform equipped with a circular solid flat heave plate. The forced oscillation tests were performed in the range of extreme and operational Keulegan–Carpenter numbers (KCs) for two different frequencies of the heave plate's oscillatory motion. A submersible two-dimensional (2D) three-component (3C) Stereoscopic Particle Image Velocimetry (Stereo-PIV) system was employed to measure the flow field velocity distribution. The Stereo-PIV images were obtained at four positions in the oscillation cycle. The investigation focused on detecting scale effects on the velocity and vorticity for the three models of different scales. Similarities in centre positions, shape, and contours between the three models were visualised for the measured velocity field. The computed vorticity field also revealed similarities in centre positions, shape, and contours among the three different scales. Following up on previous works focusing on the hydrodynamic forces on oscillating circular solid plates, the outcomes of this paper also confirm that, for the considered case study, the correct choice of the motion amplitude (KC) impacts the flow physics of the model tests more than the scale factor. Highlights: Experimental investigation of the impact of the scale factor on the flow physics of semi-submersible platforms. Similarities in centre positions, shape, and contours for the measured velocity field between three models of different scales. Similarities in centre positions, shape, and contours for the computed vorticity field between three models of different scales. The correct choice of the motion amplitude (KC) impacts the flow physics of the model tests more than the scale factor.